Penanaman Karakter Kedisiplinan, Tanggung Jawab, dan Kepatuhan Beribadah melalui Pembiasaan Sholat Dluha pada Anak Usia Dini di TK Muslimat NU Plumpang - Ria Yuliatin; Asma’ul Amiludiyah; Siti Sholika; Fashi Hatul Lisaniyah (Khirani: Jurnal Pendidikan Anak Usia Dini, 2026)
This study aims to analyze the cultivation of discipline, responsibility, and obedience in worship through the habituation of Dhuha prayer among early childhood students at TK Muslimat NU Plumpang. Character education in early childhood is fundamental in shaping children's moral and religious foundations. The habituation method is considered effective because early childhood is in the golden age phase where imitation and repetition strongly influence behavioral formation. This research employed a qualitative descriptive approach. Data were collected through observation, interviews with teachers and school principals, and documentation. The results show that the habituation of Dhuha prayer conducted routinely every morning before learning activities significantly contributes to developing discipline through punctuality and orderly preparation, responsibility through self-preparation and maintaining prayer equipment, and obedience in worship through consistent and guided prayer practice. Supporting factors include teacher role modeling, parental support, and structured school programs, while inhibiting factors involve children’s fluctuating moods and limited parental reinforcement at home. The study implies that structured religious habituation programs effectively strengthen character education in early childhood institutions.